Pemanfaatan Game Edukatif Wordwall untuk Meningkatkan Hasil Belajar Matematika - Siregar, Sakinah; Novita Sari, Dwi; Desniarti; Sari Sihite, Roymantini Novita (UNIB Press, 2025)
This classroom action research aims to improve mathematics learning outcomes on the topic of quadrilateral plane shapes among fourth-grade students at SD 060931 Medan through the use of the educational game media Wordwall. Conducted over two cycles, each comprising planning, implementation, observation, and reflection phases, the study involved 16 students and used test instruments validated by experts. Data were collected through learning outcome tests administered after each cycle. The analysis employed descriptive quantitative techniques by comparing average scores across the pre-cycle, cycle I, and cycle II. The results showed a significant improvement in student achievement: from an initial average score of 33.75 in the pre-cycle to 53.75 in cycle I (an increase of 59.26%), and further to 74.38 in cycle II (an increase of 38.37%). The total improvement from the pre-cycle to cycle II reached 120.37%. These findings indicate that Wordwall effectively enhances student engagement and understanding of geometric concepts. The study concludes that interactive and game-based media like Wordwall can significantly improve learning outcomes in mathematics, especially on abstract topics such as geometry.